All that's not fit to print - Affelt, Amy L., 1970- (Emerald Publishing Limited, 2019)
"Dewey Defeats Truman." "Hillary Clinton Adopts Alien Baby."Fake news may have reached new notoriety since the 2016 US election, but it has been around a long time. Whether it was an error in judgment in a rush to publish election results in November, 1948, or a tabloid cover designed to incite an eye roll and a chuckle in June, 1993, fake news has permeated and influenced culture since the inception of the printed press. But now, when almost every press conference at the White House contains a declaration of the evils of "fake news", evaluating information integrity and quality is more important than ever.In All That's Not Fit to Print, Amy Affelt offers tools and techniques for spotting fake news and discusses best practices for finding high quality sources, information, and data. Including an analysis of the relationship between fake news and social media, and potential remedies for viral fake news, Affelt explores the future of the press and the skills that librarians will need, not only to navigate these murky waters, but also to lead information consumers in to that future.For any librarian or information professional, or anyone who has ever felt overwhelmed by the struggle of determining the true from the false, this book is a fundamental guide to facing the tides of fake news.
Prelims -- Introduction -- References -- About the author -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Library science -- Vocational guidance; Information science -- Vocational guidance; Fake news; Truthfulness and falsehood; Libraries and mass media; Libraries and society; Language Arts & Disciplines -- Library & Information Science -- General; Library & information services